MEDIA DISKURSIDA DISKURS MARKERLARNING RETORIK ROLLARI - Albina Bazarbaeva; Isomiddinova Nilufar Ziyodullo qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Discourse markers are linguistic elements that enable coherence, guide interpretation, and shape rhetorical meaning in communicative texts. While their roles in spoken interaction and academic writing have been well documented, less research has systematically examined how discourse markers function rhetorically within media discourse. This study investigates the pragmatic and rhetorical roles of discourse markers in English-language media texts, analyzing television news transcripts, online articles, and opinion pieces to understand how these markers contribute to structuring meaning, signaling stance, and engaging audiences. Drawing on foundational frameworks by Schiffrin [Schiffrin, D., 1987] and Fraser [Fraser, B., 1999], the findings show that discourse markers perform crucial organizational, evaluative, and interactive roles, enhancing both conceptual clarity and rhetorical impact. The study highlights genre specificities in discourse marker usage and suggests implications for discourse analysis, media linguistics, and effective communication pedagogy